Combinatorial antitumor effects of indoleamine 2, 3-dioxygenase inhibitor NLG919 and paclitaxel in a murine B16-F10 melanoma model. (September 2017) - Meng, Xiangjing; Du, Guangying; Ye, Liang; Sun, Shanyue; Liu, Qiaofeng; Wang, Hongbo; Wang, Wenyan; Wu, Zimei; Tian, Jingwei
Indoleamine 2, 3-dioxygenase (IDO) is involved in tumor immune escape and resistance to chemotherapy, and is clinically correlated with tumor progression. IDO inhibitors show marginal efficacy as single agents; therefore, combinations of these inhibitors with other therapies hold promise for cancer therapy. The aim of this study was to investigate the synergistic antitumor effects of IDO inhibitor NLG919 in combination with different regimens of paclitaxel in a murine B16-F10 melanoma model. NLG919 increased the cytotoxic activity of paclitaxel toward B16-F10 cells in the presence of pretreatment with interferon (IFN)-γ in vitro. In B16-F10 tumor-bearing mice, NLG919 was uniformly distributed throughout tumors and decreased kynurenine levels and kynurenine/tryptophan ratios in tumors and plasma for 6–12 h. NLG919 suppressed tumor growth in a dose-dependent manner and exhibited maximum efficacy at 100 mg/kg. In combination with different regimens of paclitaxel, NLG919 displayed synergistic antitumor effects, and NLG919 did not increase the side effects of paclitaxel. Within the tumors, the percentage of CD3 +, CD8 +, and CD4 + T cells and secretion of IFN-γ and interleukin-2 were synergistically increased, whereas the percentage of CD4 + CD25 + regulatory T cells was decreased. NLG919 can potentiate the antitumor efficacy of paclitaxel without increasing its side effects, suggesting that the combination of IDO inhibitor-based immunotherapy with chemotherapy could be a potential strategy for cancer treatment.